Occurrence and Consumer Health Risk Assessment of Heavy Metals in Frozen Demersal Fish and Cephalopod Products from Benoa Port, Bali Province - Putu Angga Wiradana; I Made Gde Sudyadnyana Sandhika; Putu Eka Sudaryatma; I Gede Widhiantara; Made Nyandra; Adnorita Fandah Oktariani; Setyo Budi Kurniawan (Universitas Airlangga, 2024)
Introduction: Heavy metal pollution has become an important environmental issue today. This study was aimed to identify the heavy metals of the two fishing products namely demersal fish and cephalopods landed at Benoa Port, Bali Province and their health risk effects on consumers. Methods: Demersal fish and cephalopod products were obtained from local fishermen at Benoa port. Atomic Absorption Spectrophotometry (AAS) was used to specify the (Pb, Cd, and Hg) in 34 fish fillet products weighing an average of 500 grams each. Statistical software was used to conduct an analysis of the collected data, while THQ, TTHQ, and TCR were calculated and compared with USEPA regulations. Results and Discussion: The results of this research showed that the content of heavy metals in demersal fish and cephalopod products was lower than the levels suggested by official agencies in a number of countries. In populations of various ages, the target Hazard Quotient (THQ) for the heavy metal was less than 1. At this point, the Total THQ result did not imply any risk to human health from ingestion of these two fishery products. When these two products were ingested, the target cancer risk (TCR) did not represent a cancer risk. Conclusion: The outcomes of this study showed that the bioaccumulation levels of both fishery products with low levels of heavy metals are safe for human consumption.